The letter to the Ephesians - Campbell, Constantine R. (Grand Rapids, Michigan : William B. Eerdmans Publishing Company, 2023)
"A commentary on the Letter to the Ephesians that explains the text verse by verse, focusing on the theme of union with Christ"--
"A clear and comprehensive commentary on Paul's Letter to the Ephesians. In the latest Pillar New Testament Commentary, Constantine R. Campbell illuminates the Letter to the Ephesians with scholarly precision and pastoral warmth. In line with the christological concerns of the letter, Campbell calls special attention to its theme of union with Christ. His thorough analysis covers a breadth of topics, including salvation and grace, the glory of God, and the church and its mission. Aimed at students and scholars of the Pauline epistles, Campbell's commentary carefully explains each verse of Ephesians with attention to historical and linguistic context. Yet the commentary prioritizes imminent theological concerns and remains accessible to any serious reader of the New Testament"--
Includes bibliographical references and indexes.
Keywords: Bible. -- Commentaries; RELIGION / Biblical Commentary / New Testament / Paul's Letters; RELIGION / Biblical Studies / New Testament / Paul's Letters; Commentaries